DESIDOC in Pursuit of Excellence - Desidoc, Director (DESIDOC Journal of Library & Information Technology, 2003)
The Defence Scientific Information and Documentation Centre (DESIDOC) is very well-known as a central source of S&T Information for the Defence Research & Development organisation (DRDO) which has over 50 R&D laboratories located at different places in the Country.Desidoc is one of the DRDO Scientists and Technologists.The functions of DESIDOC are therefore oraginsed to meet this mandate. http://dx.doi.org/10.14429/dbit.17.2.3335